Faktor-Faktor Yang Berhubungan Dengan Kejadian Balita BGM di Desa Karangpasar Wilayah Kerja Puskesmas Tegowanu - Nurul Budi Lestari; Agus Sartono; Erma Handarsari (Jurnal Gizi, 2016)
One kind of the nutritional problem at under five years old child in Grobogan districtis is under red line (bawah garis merah/BGM). Under red line is the child who have body weight point thats located at under red line on weighing curve.. The nutritional interventions was done by Tegowanu public health center to reduce the incidence of BGM. That intervention can reducethe percentation of BGM from 2,35% in 2012 to 1,45% in 2013. Thats can reduce the number of BGM at 17 villages from 18 villages coverage by Tegowanu Public Health Centre. The incidence of BGM at one of the villages, is Karangpasar village cannot be reduce yet. The percentation of BGM at Karanganyar Village is still high. That is 8,45 % more hight than the target ofincreasing the number of BGM in Grobogan District, less than 5%. The purpose of the researh is to analysis factors thats related with incident of BGM.The kind of the research is analityc with cross sectional approach and survey method. The research population is families with under five years old child, who live at Karangpasar village. The number of sample are 74 families with under five years old child, 14 BGM and 60 not BGM. Employment status, income level and the level of nutrition knowledge measured by questionnaire while the BGM status of under five years old child was measured by looking at the KMS Chi-square test will be done to analysis the relationship.of variables.The result of this study show there are 14 (81,1%) of under five years old child who BGM. The level of women work participation by respondent is hight (78,4%). The family income level ofthe respondents on average Rp.1.066.000,00 per capita per month Rp.466,391. There is no families with low income. The nutritional knowledge level of the respondents on average 74,54% 17,950% in which 58,1 % mothers have moderate and low nutrition knowledge level. Khai square test results indicated that mother employment status, family income level, and the level of mothers nutritional knowledge related with the incidence of BGM .While the family income level have the strongest relationship.Keyword : Incident of BGM, Under five years old child, mothers employment status, mothers nutritional knowledge level, family income